Answer(s):
Exact Form: x + 2 y − 3 z = 15 , 2 x − 2 z = 6 , 3 2 3
Mixed Number Form: x + 2 y − 3 z = 15 , 2 x − 2 z = 6 , 3 2 3
Improper Fraction Form: x + 2 y − 3 z = 15 , 2 x − 2 z = 6 , 11 3
Decimal Form: x + 2 y − 3 z = 15 , 2 x − 2 z = 6 , 3. ¯ 6
Hope this helps, have a nice day/night! :D
Answer:
y = 89 x = 123
Step-by-step explanation:
since they're both in standard form, its easier to do the process of elimination
x - y = 34
-x -y -212
------------------
-2y = -178
y = 89
now plug in y to any one of those two equations
x - y = 34
x - 89 = 34
x = 123
<em>to check:</em>
<em>x</em><em> </em><em>+</em><em> </em><em>y</em><em> </em><em>=</em><em> </em><em>2</em><em>1</em><em>2</em>
<em>1</em><em>2</em><em>3</em><em> </em><em>+</em><em> </em><em>8</em><em>9</em><em> </em><em>=</em><em> </em><em>2</em><em>1</em><em>2</em>
<em>2</em><em>1</em><em>2</em><em> </em><em>=</em><em> </em><em>2</em><em>1</em><em>2</em>
In order to do this you have to substitute b with 9 and get 3a+9=54, now subtract 9 from both sides to leave a by itself and get 3a=45, now divide 3 in both sides to leave a by itself and get a=15
Hope this helps
Answer:
195
Step-by-step explanation:
To find the 23rd term of this sequence, we can use the arithmetic sequence formula where,
= term
= first term
= term position
= common difference